Estudo da classificação não-destrutiva de peças serradas de espécies cultivadas no Brasil para uso em estruturas - Candian, Marcela (2007)
This research had for purpose comparatively to verify the accuracy of the techniques of transverse vibration and ultrasound to the values gotten in static testings, for sawed wood used in structures. With the results gotten in the development of the present research it was possible to calibrate the coefficient of modification (kmod, 3) of NBR 7190:1997, besides increasing the relative knowledge to the nondestructive tests in wood. In the experimental methodology studies with parts of structural members of Eucalyptus grandis, Eucalyptus citriodora, Pinus sp and Goupia glabra had been carried through, which had been classified using the techniques of ultrasound and transverse vibration, for the determination of the dynamic modulus of elasticity (Ed). Simultaneously to the tests with ultrasound they had been carried through the visual grading and tests of static bending (MOE). The values of coefficient of determination for the technique of transverse vibration (R² = 0,75, R² = 0,80, R² = 0,93 and R² = 0,89) and for the technique of ultrasound (R2 = 0,65, R2 = 0,76, R2 = 0,66 and R2 = 0,88), gotten respectively for the Eucalyptus grandis, Eucalyptus citriodora, Pinus sp and Goupia glabra are significant, demonstrating that the techniques of ultrasound and transverse vibration are important tools for nondestructive inference of the modulus of elasticity of wood. The technique of transverse vibration presented better resulted in relation to the ultrasound, therefore it presents one better tack enters the physical model of the phenomenon and the corresponding associated mathematical model. In the determination of the values of coefficient of modification kmod, 3, was verified that the technique of transverse vibration presented superior values of coefficient in relation the ultrasound technique, therefore allows a classification next to the values gotten in the static bending.